Administrative Law in the Time of Corona(virus):: Resilience and Trust-building - Hoffman, István; Balázs, István (Public Governance, Administration and Finances Law Review, 2021)
The Hungarian administrative law has been significantly impacted by the Covid-19 pandemic. Several rules – which were introduced during the state of danger based on the epidemic situation – have been incorporated into the Hungarian legal system. The administrative procedural law has been influenced by the epidemic transformation. However, the rules on e-administration have not been reformed significantly (due to the digitalisation reforms of the last years), but the rules on administrative licenses and permissions have been amended. The priority of the general code on administrative procedure has been weakened: new, simplified procedure and regime have been introduced. The local self-governance has been impacted by the reforms. The transformation has had two, opposite trends. On the one hand, the Hungarian administrative system became more centralised during the last year: municipal revenues and task performance have been partly centralised. The Hungarian municipal system has been concentrated, as well. The role of the second-tier government, the counties (megye), has been strengthened by the establishment of the special economic (investment) zones. On the other hand, the municipalities could be interpreted as a ‘trash can’ of the Hungarian public administration: they received new, mainly unpopular competences on the restrictions related to the pandemic. Although these changes have been related to the current epidemic situation, it seems, that the ‘legislative background’ of the pandemic offered an opportunity to the central government to pass significant reforms. From 2021 a new phenomenon can be observed: the state of danger has remained, but the majority of the restrictions have been terminated by the Government of Hungary. Therefore, the justification of the state of danger during the summer of 2021 became controversial in Hungarian public discourse.